Up Came a Squatter : Niel Black of Glenormiston, 1839-1880. - Black, Maggie (University of New South Wales Press, 2016)
Niel Black, a Scot from Argyllshire, arrived in Melbourne in September intending to make his fortune. Ambitious and determined, Black became one of the most successful and energetic squatters in the Western District of Victoria - a livestock breeder and a Member of the Legislative Council. He was also a correspondent extraordinaire, and his letters to family, fellow pastoralists, colonial officials, and his chief UK business partner, Thomas Steuart Gladstone (and first cousin of the British prime minister), offer a unique insight into the time. Black's letters and journals, now held at the State Library of Victoria, are the inspiration for this revelatory book written by his great-granddaughter. --Provided by publisher.